(3TQM GHf YUahQ Ydi cJGH GdLed ddRLGLis - (3CHh GdMSf Ydj Hf eDef GdETHjdi GdeYQha HGHf YUahQ GdMVQeis; (3YHO GdQMef Hf ESMGb GdfgGhfOj GdRLGLj, CHh GdbGSe,J (B377 (3g`s ((3eMeO Hf eDef GdHLGhi GdeZQHj GdeGdcj s)
(3ChdgG (B:s
(3bhd CHj GdbGSe CbSGe GdcdGe KdGKI CbSGe GdcdGe eVGa heVGa Edjg dGjYde GdeVGa ef MjK gh eVGa MJi JYde eG CVja Edjg ajfHZi Cf fHjf ChdkG GdcdGe s
(3BNQgG (B:s
(3YdeGA YRdg NGdO dEbGeI GdhRf dCfge jMPahfgG ai GdcdGe ajbhdhf YdeGA Hfh adGf Je GdcJGH HMeO Gddg hefg s
(3GdfSNI HgG MhGTs
(3dgG fSNI CNQi eagQSI JMJ Qbe (B71 (3fMhs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdfMhs